A Review: Bacterial Pustule of Soybean Caused by Xanthomonas Axonopodis Pv. Glycines: Epidemiology, Economic Impact, and Status in Indonesia - Zahra Tazkiyatun Haqiki; Hadiwiyono Hadiwiyono (Journal of Biodiversity and Biotechnology, 2025)
Soybeans (Glycine max L. Merrill) are the most important commodity after rice and corn. Soybeans are used as food, feed, and materials for the food industry. One of the major biological constraints to soybean productivity is bacterial pustule disease caused by Xanthomonas axonopodis pv. glycines (Xag), a pathogen favored by warm and humid environments. This review synthesizes current knowledge on the epidemiology, pathogenesis, and economic losses associated with soybean bacterial pustule, with particular emphasis on its status in Indonesia. Available studies indicate that bacterial pustule is widely distributed in major soybean-producing regions, with reported disease severity ranging from 12% to 70%. Under favorable environmental conditions, yield losses may reach 7–40%, primarily due to defoliation, reduced photosynthetic efficiency, and decreased seed size and number. Disease development is strongly associated with temperatures of 26–30 °C, high relative humidity, and prolonged leaf wetness, conditions commonly observed during the rainy season in tropical agroecosystems. Indonesia’s warm and humid tropical climate provides suitable conditions for pathogen survival, dispersal, and infection, particularly during the rainy season. This review highlights key knowledge gaps and underscores the need for integrated epidemiological assessments to mitigate yield losses and to support sustainable soybean production in Indonesia.